1964
DOI: 10.1126/science.143.3604.366
|View full text |Cite
|
Sign up to set email alerts
|

Microsporum nanum : First Recorded Isolation from Animals in the United States

Abstract: The first cases in the United States of swine infections caused by the fungus Microsporum nanum are reported. The infections occurred in a herd of Yorkshire swine in Pennsylvania. The dermatophyte, which readily produced experimental infections, was identified by isolation and studies in pure cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…An outbreak of swine ringworm in Centre County, Pa, in 1964, caused by M nanum was reported by Bubash et al 9 Ginther et al10,11 also reported swine infections in Kansas, Kentucky, New Jersey, and Pennsyl¬ vania. Early in 1964, Ginther and Ajello 12 discussed the prevalence of this organism in the United States and recorded its isolation from soil and swine in 12 states, including Texas.…”
mentioning
confidence: 99%
“…An outbreak of swine ringworm in Centre County, Pa, in 1964, caused by M nanum was reported by Bubash et al 9 Ginther et al10,11 also reported swine infections in Kansas, Kentucky, New Jersey, and Pennsyl¬ vania. Early in 1964, Ginther and Ajello 12 discussed the prevalence of this organism in the United States and recorded its isolation from soil and swine in 12 states, including Texas.…”
mentioning
confidence: 99%